O monitoramento fiscal como indutor de comportamento dos contribuintes de ICMS do Estado do Ceará - Mesquita, Alexandre Fonte de (2014)
This present study we sought show the activity of Tax Monitoring adopted during the last years for Department of Finance of the States and Federal with alternative tool in the fighting tax evasion. The emphasis this work is in Tax Monitoring executed for Department of Finance of the State of Ceará. The main objectives this work was does investigation impacts of Tax Monitoring on behavior of taxpayers using with explanatory variable the collection of ICMS. For that, we used the method econometric “difference in difference”, which a information database from the Department of Finance of the State of Ceará and the records dates was omited because tax secrecy. The results shows that coefficient were not significant statistically for economic segments of industry, retail sale and trasnport, but, the results indicate that Tax Monitoring promoted for the wholesale segment a positive impact of 73% on the collection of ICMS.